Secondary Prevention Program through Hybrid Tele-Cardiac Rehabilitation using a Combination of Vigorous-intensity Interval Training and Low-Intensity Home-based Exercise in Patient with Refractory Angina Post-Percutaneous Coronary Intervention - Nazir, Arnengsih; Anggraini, Gabriela; Nurhalizah, Hana Athaya (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background: Refractory angina (RA) refers to symptoms lasting >3 months due to reversible ischemia occurring with coronary artery disease, which cannot be controlled by increased medical therapy or revascularization including percutaneous coronary intervention (PCI). It may result in a significant impact on patient outcomes such as exercise limitation, biopsychosocial disorders, and decreased quality of life. Participation of patients with RA in cardiac rehabilitation (CR) reduces angina frequency and increases exercise capacity. Exercise-based CR also improves endothelial function, reduces oxidative stress and arterial stiffness, and improves myocardial perfusion. CR is also known as a secondary prevention program with the main goal to help patients return to their normal activities by increasing their functional capacity and preventing long-term complications. Case illustration: A 64-year-old male has undergone PCI and experienced RA. This patient was given a CR program to increase his functional capacity as a secondary prevention of cardiovascular disease through a center-based combined with a home-based CR program. Aerobic exercise given was hospital-based vigorous-intensity interval training and low-intensity home-based exercise. Problems found were refractory angina that often appeared during activity, and low cardiorespiratory endurance or muscular fitness. Angina symptoms and hand grip strength improved after 2 weeks, even though muscular fitness classification was still poor. During the program, he could achieve the exercise heart rate target without any symptoms. After 4 weeks, hand grip strength and physical activity were improved, and an exercise test revealed no symptoms during the test, appropriate hemodynamic response, and good fitness classification. However, there were still frequent VES with couplet episodes, so the patient was still classified as high-risk stratification. Although risk stratification was still high, the patient was allowed to enter phase III CR, with the prescription of moderate-intensity aerobic, low-intensity resistance, flexibility, and breathing exercises. These exercises were given based on recommendations for the average adult to maintain his level of physical activity and promote lifelong healthy behavior. Conclusion: Hybrid tele-cardiac rehabilitation through a combination of vigorous-intensity interval training and low-intensity home-based exercise in a patient with refractory angina post-PCI improved functional capacity as a key component for the prevention of long-term cardiac or non-cardiac complications.